Protocol for cluster randomized evaluation of reaching married adolescents - a gender-synchronized intervention to increase modern contraceptive use among married adolescent girls and young women and their husbands in Niger - Sneha Challa; Stephanie M. DeLong; Nicole Carter; Nicole Johns; Holly Shakya; Sabrina C. Boyce; Ricardo Vera-Monroy; Sani Aliou; Fatouma A. Ibrahima; Mohamad I. Brooks; Caitlin Corneliess; Claire Moodie; et al. (BMC, 2019)
Abstract Background Early marriage and early childbearing are highly prevalent in Niger with 75% of girls married before age 18 years and 42% of girls giving birth between ages 15 and 18 years. In 2012, only 7% of all 15-19-year-old married adolescents (male and female) reported use of a modern contraceptive method with barriers including misinformation, and social norms unsupportive of contraception. To meet the needs of married adolescents and their husbands in Niger, the Reaching Married Adolescents (RMA) program was developed with the goal of improving modern contraceptive method uptake in the Dosso region of Niger. Methods Using a four-arm cluster randomized control design, the RMA study seeks to assess whether household visits only (Arm 1), small group discussions only (Arm 2), or a combination of both (Arm 3), as compared to controls (no intervention - Arm 4), improve modern contraceptive method use among married adolescent girls and young women (AGYW), age 13-19 years-old, in three districts of the Dosso region. Intervention conditions were randomly assigned across the three districts, Dosso, Doutchi, and Loga. Within each district, eligible villages were assigned to either that intervention condition or to the control condition (12 intervention and 4 control per district). Across the three intervention conditions, community dialogues regarding modern contraceptive use were also implemented. Data for the study was collected at baseline (April - June 2016), at 24 months post-intervention (April - June 2018), and a final round of data collection will occur at 40 months post-intervention (October - December 2019). Discussion The RMA intervention is a gender-synchronized and community-based program implemented among married adolescent girls and their husbands in the context of rural Niger. The intervention is designed to provide education about modern contraception and to promote gender equity in order to increase uptake of modern contraceptive methods. Results from this cluster randomized control study will contribute to the knowledge base regarding the utility of male engagement as a strategy within community-level approaches to promote modern contraceptive method use in the high need context of West Africa. Trial registration Registered October 2017 - ClinicalTrials.gov NCT03226730.